Cover Design for Osseointegrated Prostheses - Hörling, Anton; Uriarte Peña, Iñigo (My University, 2020)
This paper reports the design process of a cover for osseointegrated myoelectric prostheses. The main purpose of these prostheses is to rehabilitate amputees by restoring as much of the lost function as possible and this is thus what previous development has focused on primarily. Consequently, aesthetic considerations have been neglected, and, whilst the functional usability may be the major benefactor for psychological acceptance of the prostheses, it has lately been suggested that the appearances also have an affect; that more novel designs, regarding the prostheses as ornaments rather than replicas, could further enhance perceived quality of life by having a positive impact on how amputees see themselves as well as how others look at their disability. The idea that quality of life for the amputees could be increased by the aesthetics of prostheses was what motivated the project. To understand how the external design alters the experience of wearing and encountering a prosthesis, relevant scientific publications were reviewed, and perspectives of amputees studied in presence on social media and through interviews. A concept designed for an enhanced experience of use, satisfying of the criteria elicited in the research, was then developed iteratively though ideation and prototyping. The result is a functional prototype